Preparation method and application of aramid pulp modified battery separator
Patent Information
- Application Number
- CN202611465605.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明针对以上现有技术中聚烯烃电池隔膜孔隙率低、抗穿刺能力差,以及表面涂覆改性聚烯烃电池隔膜界面结合力弱等问题,提出一种片材、电池隔膜、其制备方法和应用
[0064]本发明通过精磨和高频疏解的作用,将芳纶浆粕均匀分散于聚乙烯中,再基于高、低密度聚乙烯之间的相似相容和共结晶现象,可原位制得具有高相容性的以芳纶浆粕改性的低密度聚乙烯为芯层、高密度聚乙烯为内、和/或外表层的两层或三层片材;随后采用梯度双向同步拉伸工艺,经取向增强、应力集中、均匀成孔步骤,可实现以芳纶浆粕为应力集中点的芳纶浆粕改性电池隔膜的制备,本发明的电池隔膜与聚烯烃类电池隔膜相比,在抗穿刺、孔隙率、孔径尺寸、充放电比容量损失等方面皆具有明显改善,可解决传统锂离子电池的能量密度瓶颈,助力高功率的锂硫电池的产业化开发。
Smart Images

Figure FT_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials, specifically relating to a sheet, a battery separator, its preparation method, and its application. Background Technology
[0002] As the global energy structure shifts towards cleaner and lower-carbon energy, lithium-ion batteries, as high-efficiency energy storage devices, play a central role in electric vehicles, consumer electronics, and renewable energy storage. The battery separator, as a key component of lithium-ion batteries, primarily functions to facilitate ion conduction and provide electronic insulation. It ensures the normal conduction of electrochemical reactions and prevents short circuits caused by direct contact between the positive and negative electrodes. Therefore, the battery separator directly affects the battery's safety, energy density, and cycle life.
[0003] Currently, polyolefin-based films remain the most widely used battery separators across various applications, primarily including single-layer or multi-layer composite films made of polyethylene and polypropylene. However, polyolefin-based battery separators are prone to shrinkage and deformation upon heating, and have low porosity. During battery charge-discharge cycles, they cannot effectively block the diffusion of polysulfide ions, leading to the deposition of intermediates on the lithium anode surface. This results in significant losses of active material, severely impacting the practicality and development of lithium-sulfur batteries. Therefore, developing novel, high-quality separator materials is urgently needed to improve the structural stability of lithium-sulfur batteries, increase their capacity, suppress polysulfide ion deposition, and inhibit lithium dendrite penetration. Summary of the Invention
[0004] This invention addresses the problems of low porosity, poor puncture resistance, and weak interfacial adhesion in surface-coated modified polyolefin battery separators in existing technologies. It proposes a sheet material, a battery separator, its preparation method, and its applications. Based on similar compatibility and eutectic behavior, this invention proposes a highly compatible aramid pulp / polyethylene three-layer sheet molding process. Based on the principle of stress concentration, it utilizes biaxial stretching for film formation and pore creation, applying this process to the field of battery separators.
[0005] Specifically, one aspect of the present invention provides a sheet comprising a core layer and a coating layer on one or both surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene.
[0006] In one or more embodiments, the aramid pulp has a Canadian fraction of 300-500 mL and a specific surface area of 6.00-12.00 m². 2 / g.
[0007] In one or more embodiments, the high-density polyethylene has a density of 0.94-0.96 g / cm³. 3It has a melting point of 130-137℃ and a melt index of 3-15g / 10min.
[0008] In one or more embodiments, the low-density polyethylene has a density of 0.91-0.93 g / cm³. 3 It has a melting point of 105-115℃ and a melt index of 3-10g / 10min.
[0009] In one or more embodiments, the length of both the aramid pulp and the low-density polyethylene in the core layer is 50-200 nm.
[0010] In one or more embodiments, the mass ratio of aramid pulp to low-density polyethylene in the core layer is 1:(0.1-10).
[0011] In one or more embodiments, the thickness of the core layer is 100-150 μm.
[0012] In one or more embodiments, the thickness of the core layer is 108-130 μm.
[0013] In one or more embodiments, the thickness of the coating layer is 10-100 μm.
[0014] In one or more embodiments, the thickness of the coating layer is 20-50 μm.
[0015] In one or more embodiments, the sheet has a thickness of 110-350 μm.
[0016] In one or more embodiments, the sheet has a thickness of 128-230 μm.
[0017] In one or more embodiments, the interlaminar shear strength of the sheet is ≥45MPa.
[0018] In one or more embodiments, the sheet has a puncture resistance of ≥14N.
[0019] Another aspect of the present invention provides a method for preparing the sheet material according to any embodiment of the present invention, the method comprising dispersing aramid pulp and low-density polyethylene in water to obtain a suspension, fine grinding and loosening, preparing a core layer by coating and drying, preheating the core layer, coating one or two surfaces of the core layer with high-density polyethylene, and preparing the sheet material by co-crystallization.
[0020] In one or more embodiments, the mass fraction of the aramid pulp and low-density polyethylene in the suspension is 8%-15%; wherein the mass fraction of the aramid pulp in the suspension is 0.1%-14.9%, and the mass fraction of the low-density polyethylene in the suspension is 0.1%-14.9%.
[0021] In one or more embodiments, the fine grinding is nano-fine grinding.
[0022] In one or more embodiments, the shunting is high-frequency shunting.
[0023] In one or more embodiments, the drying temperature of the coating drying method is 80-90°C; the vacuum degree of the coating drying method is 10-1000Pa; and the drying time of the coating drying method is 12-24h.
[0024] In one or more embodiments, the preheating temperature is 110-150°C.
[0025] In one or more embodiments, the preheating temperature is 120-140°C.
[0026] In one or more embodiments, the co-crystallization temperature is 80-130°C.
[0027] In one or more embodiments, the co-crystallization temperature is 90-110°C.
[0028] In one or more embodiments, the co-crystallization time is 1-20 min.
[0029] In one or more embodiments, the co-crystallization time is 3-10 minutes.
[0030] In one or more embodiments, the length of both the aramid pulp and the low-density polyethylene after fine grinding is 50-200 nm.
[0031] Another aspect of the present invention provides a battery separator comprising a core layer and a coating layer on one or both surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene.
[0032] In one or more embodiments, the battery separator is prepared using the sheet material described in any embodiment of the present invention.
[0033] In one or more embodiments, the aramid pulp has a Canadian fraction of 300-500 mL and a specific surface area of 6.00-12.00 m². 2 / g.
[0034] In one or more embodiments, the high-density polyethylene has a density of 0.94-0.96 g / cm³. 3 It has a melting point of 130-137℃ and a melt index of 3-15g / 10min.
[0035] In one or more embodiments, the low-density polyethylene has a density of 0.91-0.93 g / cm³. 3 It has a melting point of 105-115℃ and a melt index of 3-10g / 10min.
[0036] In one or more embodiments, the porosity of the battery separator is 40-60%.
[0037] In one or more embodiments, the porosity of the battery separator is 47-58%.
[0038] In one or more embodiments, the length of both the aramid pulp and the low-density polyethylene in the core layer is 50-200 nm.
[0039] In one or more embodiments, the mass ratio of aramid pulp to low-density polyethylene in the core layer is 1:(0.1-10).
[0040] In one or more embodiments, the thickness of the battery separator is 13-17 μm.
[0041] In one or more embodiments, the average pore size of the battery separator is less than 1 μm.
[0042] In one or more embodiments, the average pore size of the battery separator is 620-740 nm.
[0043] In one or more embodiments, the interlaminar shear strength of the battery separator is 40-50 MPa.
[0044] In one or more embodiments, the battery separator has a puncture resistance of 4.0-6.0N.
[0045] Another aspect of the present invention provides a method for preparing a battery separator according to any embodiment of the present invention, the method comprising creating pores in a sheet according to any embodiment of the present invention to obtain a battery separator.
[0046] In one or more embodiments, the method further includes the step of preparing the sheet using the method described in any embodiment of the present invention.
[0047] In one or more embodiments, the perforation includes the following steps: S1: Preheated sheet; and S2: Synchronous bidirectional stretching.
[0048] In one or more embodiments, the synchronous biaxial stretching temperature is 85-100℃, the stretching rate is 30-100% / s, the stretching ratio is 1.5-5.0, the heat setting temperature is 85-100℃, and the heat setting time is 10-240s.
[0049] In one or more embodiments, in step S1, the preheating temperature is 50-70°C.
[0050] In one or more embodiments, in step S1, the preheating temperature is 60-70°C.
[0051] In one or more embodiments, in step S1, the preheating time is 20-60 seconds.
[0052] In one or more embodiments, in step S1, the preheating time is 20-40 seconds.
[0053] In one or more embodiments, in step S2, three simultaneous biaxial stretching operations are performed; the temperatures of the second and third simultaneous biaxial stretching operations are both higher than the temperature of the first simultaneous biaxial stretching operation, and the temperatures of the second and third simultaneous biaxial stretching operations are the same or different; and / or, the stretching rates of the first and second simultaneous biaxial stretching operations are both higher than the stretching rate of the third simultaneous biaxial stretching operation; and / or, the stretching ratio of the second simultaneous biaxial stretching operation is greater than the stretching ratio of the first simultaneous biaxial stretching operation, and the stretching ratio of the third simultaneous biaxial stretching operation is greater than the stretching ratio of the second simultaneous biaxial stretching operation; and / or, the heat setting temperatures of the first and second simultaneous biaxial stretching operations are higher than the heat setting temperature of the third simultaneous biaxial stretching operation, the heat setting temperature of the second simultaneous biaxial stretching operation is higher than the heat setting temperature of the first simultaneous biaxial stretching operation, the heat setting temperature of the first simultaneous biaxial stretching operation is the same or different from the temperature of the first simultaneous biaxial stretching operation, and the heat setting temperature of the second simultaneous biaxial stretching operation is the same or different from the temperature of the second simultaneous biaxial stretching operation; and / or, the heat setting time of the third simultaneous biaxial stretching operation is greater than the heat setting time of the first and second simultaneous biaxial stretching operations.
[0054] In one or more embodiments, in step S2, the temperature of the first synchronous biaxial stretching is 85-95℃; the stretching rate is 50-100% / s; the stretch ratio is 1.5-2.0; the heat setting time is 10-60s; and the heat setting temperature is 85-95℃. The temperature of the second synchronous biaxial stretching is 90-100℃; the stretching rate is 50-100% / s; the stretch ratio is 2.1-2.5; the heat setting time is 20-60s; and the heat setting temperature is 90-100℃. The temperature of the third synchronous biaxial stretching is 90-100℃; the stretching rate is 30-60% / s; the stretch ratio is 3.0-5.0; the heat setting time is 60-240s; and the heat setting temperature is 70-90℃.
[0055] In one or more embodiments, in step S2, the temperature of the first synchronous biaxial stretching is 85-90℃; the stretching rate is 60-90% / s; the stretching ratio is 1.8-2.0; the heat setting time is 10-30s; and the heat setting temperature is 85-90℃. The temperature of the second synchronous biaxial stretching is 95-100℃; the stretching rate is 80-100% / s; the stretching ratio is 2.1-2.3; the heat setting time is 40-60s; and the heat setting temperature is 95-100℃. The temperature of the third synchronous biaxial stretching is 95-100℃; the stretching rate is 30-50% / s; the stretching ratio is 3.0-4.0; the heat setting time is 100-150s; and the heat setting temperature is 70-80℃.
[0056] Another aspect of the present invention provides a lithium-ion battery comprising the battery separator described in any embodiment of the present invention.
[0057] In one or more embodiments, the lithium-ion battery is a lithium-sulfur battery.
[0058] In one or more embodiments, the lithium-ion battery exhibits a specific capacity loss rate of less than 1% after 500 charge-discharge cycles.
[0059] Another aspect of the present invention provides the application of the sheet material described in any embodiment of the present invention in improving the puncture resistance and porosity of battery separators and reducing the specific capacity loss rate during battery charge-discharge cycles.
[0060] Another aspect of the present invention provides the use of the sheet described in any embodiment of the present invention in the preparation of battery separators.
[0061] Another aspect of the invention provides the use of low-density polyethylene, aramid pulp and high-density polyethylene in the preparation of battery separators.
[0062] In one or more embodiments, the low-density polyethylene, aramid pulp, and high-density polyethylene are as described in any embodiment of the present invention.
[0063] In the application of the present invention, the interlaminar shear strength of the battery separator is 40-50 MPa, the puncture resistance is 4.0-6.0 N, and the battery prepared therefrom, after 500 charge-discharge cycle tests, has a specific capacity loss rate of less than 1%.
[0064] This invention utilizes fine grinding and high-frequency dispersion to uniformly disperse aramid pulp in polyethylene. Based on the similar compatibility and co-crystallization between high-density and low-density polyethylene, a two- or three-layer sheet material with high compatibility, consisting of low-density polyethylene modified with aramid pulp as the core layer and high-density polyethylene as the inner and / or outer layers, can be prepared in situ. Subsequently, a gradient bidirectional synchronous stretching process is employed, involving orientation reinforcement, stress concentration, and uniform pore formation steps, to achieve the preparation of an aramid pulp-modified battery separator with aramid pulp as the stress concentration point. Compared with polyolefin battery separators, the battery separator of this invention shows significant improvements in puncture resistance, porosity, pore size, and charge / discharge specific capacity loss, which can solve the energy density bottleneck of traditional lithium-ion batteries and facilitate the industrialization development of high-power lithium-sulfur batteries. Attached Figure Description
[0065] Figure 1 This is a schematic diagram of the preparation process of the battery separator in Example 1 of the present invention. Detailed Implementation
[0066] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used herein are explained and defined in general terms below. Unless otherwise specified, all technical and scientific terms used herein have the common meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0067] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0068] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.
[0069] In this document, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0070] Unless otherwise specified, percentages refer to mass percentages and proportions refer to mass ratios in this article.
[0071] In this article, the sum of the percentages of all components in the composition is 100%.
[0072] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope defined by this invention.
[0073] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0074] In this invention, the length of aramid pulp and low-density polyethylene refers to the length of aramid pulp or low-density polyethylene that has a fibrous structure after nano-milling.
[0075] Sheet
[0076] This invention provides a sheet material comprising a core layer and a coating layer on one or both surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene. The sheet material of this invention, through the synergistic effect of eutectic behavior and similar compatibility mechanisms, can achieve an interlaminar shear strength of over 45 MPa and a puncture resistance of over 14 N.
[0077] Aramid pulp is a differentiated product of aramid fibers. Aramid pulp is a composite reinforcing fiber obtained by surface microfibrillation treatment of aramid fibers. Its surface exhibits a fluffy, ultrafine microfibrillated structure, and its main components are poly(m-phenylene isophthalamide) and / or poly(p-phenylene terephthalamide), possessing characteristics such as large specific surface area, high temperature resistance (long-term operating temperature up to 250℃), and corrosion resistance. The aramid pulp in this invention is preferably obtained by the following method: cutting aramid filament fibers, then dispersing them in water and mechanically beating and pulping them to tear the fibers and achieve fibrillation. The aramid pulp obtained through this special molding process not only possesses a series of advantages of aramid filament fibers, such as high strength, high modulus, insulation properties, and high temperature resistance, but also endows the aramid pulp surface with abundant amino groups, which can significantly improve the interfacial bonding force of aramid pulp-based composite materials. Therefore, this invention, by preparing battery separators by combining aramid pulp with polyolefins, can overcome the problems of insufficient thermal stability and puncture resistance existing in traditional polyolefin battery separators.
[0078] In some embodiments, the aramid pulp suitable for use in this invention has the following characteristics: a Canadian fraction of 300-500 mL, for example, 300 mL, 310 mL, 320 mL, 330 mL, 340 mL, 350 mL, 360 mL, 370 mL, 380 mL, 390 mL, 400 mL, 410 mL, 420 mL, 430 mL, 440 mL, 450 mL, 460 mL, 470 mL, 480 mL, 490 mL, 500 mL, or any range between two such values; and a specific surface area of 6.00-12.00 m². 2 / g, for example 6.00m 2 / g, 6.50m 2 / g, 7.00m 2 / g, 7.50m 2 / g、8.00m 2 / g, 8.50m 2 / g, 9.00m 2 / g, 9.50m 2 / g, 10.00m 2 / g, 10.50m 2 / g, 11.00m 2 / g, 11.50m 2 / g, 12.00m 2 / g or any range between two values.
[0079] The aramid pulp used herein can be any of the various aramid pulp products known in the art. Aramid pulps suitable for use herein are available commercially available. Exemplary aramid pulps include, but are not limited to, aramid 1414 pulp produced by Sinochem High Performance Fiber Materials Co., Ltd., aramid 1414 pulp from Taihe New Materials, and aramid 1313 pulp from Taihe New Materials. It should be understood that mixtures of one or more aramid pulps may be used. In some embodiments, the aramid pulp suitable for use in this invention has the following characteristics before being processed by a nano-milling machine: a fiber length of 0.95-1.35 mm, for example, 0.95 mm, 1.00 mm, 1.05 mm, 1.10 mm, 1.15 mm, 1.20 mm, 1.25 mm, 1.30 mm, 1.35 mm, or any two of these values; and a moisture content of 4.00-8.00%, for example, 4.00%, 4.50%, 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50%, 8.00%, or any two of these values.
[0080] Low-density polyethylene (LDPE), also known as high-density polyethylene, is the lightest type of polyethylene resin, with a density of 0.91-0.93 g / cm³. It appears as milky white, tasteless, odorless, non-toxic, and matte waxy granules. It possesses good flexibility, extensibility, electrical insulation, transparency, ease of processing, and some air permeability. It also exhibits good chemical stability, being resistant to alkalis and common organic solvents.
[0081] The low-density polyethylene used herein can be any of the various low-density polyethylene products known in the art. Low-density polyethylenes suitable for use herein are available commercially available. Exemplary low-density polyethylenes include, but are not limited to, 7047 produced by Daqing Petrochemical Corporation, 3224 produced by Formosa Plastics Corporation, 9020 produced by Tianjin United Corporation, and 1801 produced by Yangzi Petrochemical Corporation. It should be understood that mixtures of one or more low-density polyethylenes may be used.
[0082] In some embodiments, the low-density polyethylene suitable for use in this invention has the following characteristics: a density of 0.91-0.93 g / cm³. 3 For example, 0.91 g / cm³ 3 0.915g / cm 3 0.92g / cm 3 0.925g / cm 3 0.93g / cm 3 And the range between any two values; melting point is 105-115℃, such as 105℃, 106℃, 107℃, 108℃, 109℃, 110℃, 111℃, 112℃, 113℃, 114℃, 115℃ or any range between two values; melt index is 3-10g / 10min, such as 3g / 10min, 3.5g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, 5.5g / 10min, 6g / 10min, 6.5g / 10min, 7g / 10min, 7.5g / 10min, 8g / 10min, 8.5g / 10min, 9g / 10min, 9.5g / 10min, 10g / 10min or any range between two values.
[0083] High-density polyethylene (HDPE) is a white powder or granular product. It is non-toxic and odorless, with a density of 0.94-0.96 g / cm³, a crystallinity of 80%-90%, a melting point of 130-137℃, and a service temperature up to 100℃. Its hardness, tensile strength, and creep resistance are superior to low-density polyethylene (LDPE). It also exhibits good abrasion resistance, electrical insulation, toughness, and cold resistance. It has good chemical stability, is insoluble in any organic solvent at room temperature, and is resistant to corrosion from acids, alkalis, and various salts. Its films have low permeability to water vapor and air, and low water absorption. However, it has poor aging resistance and is less resistant to environmental stress cracking than LDPE.
[0084] The high-density polyethylene used herein can be any of the high-density polyethylene products known in the art. Commercially available high-density polyethylenes suitable for use herein are available. Exemplary high-density polyethylenes include, but are not limited to, 5200B, 2200J, and 5000S produced by Daqing Petrochemical Company; 5502, TR144, and TR480 produced by Shanghai Jinfei; 7000F produced by Yangzi Petrochemical; and 9001 produced by Plastics. It should be understood that mixtures of one or more high-density polyethylenes may be used.
[0085] In some embodiments, the high-density polyethylene suitable for use in this invention has the following characteristics: a density of 0.94-0.96 g / cm³. 3 For example, 0.94 g / cm³ 3 0.945g / cm 3 0.95g / cm 3 0.955g / cm 3 0.96g / cm 3 Or a range between any two values; melting point is 130-137℃, such as 130℃, 131℃, 132℃, 133℃, 134℃, 135℃, 136℃, 137℃ or any range between two values; melt index is 3-15g / 10min, such as 3g / 10min, 3.5g / 10min, 4g / 10min, 4.5g / 10min, 5g / 10min, 5.5g / 10min, 6g / 10min, 6.5g / 10min, 7g / 10min. 10 min, 7.5 g / 10 min, 8 g / 10 min, 8.5 g / 10 min, 9 g / 10 min, 9.5 g / 10 min, 10 g / 10 min, 10.5 g / 10 min, 11 g / 10 min, 11.5 g / 10 min, 12 g / 10 min, 12.5 g / 10 min, 13 g / 10 min, 13.5 g / 10 min, 14 g / 10 min, 14.5 g / 10 min, 15 g / 10 min, or any range between two values.
[0086] In the sheet material of the present invention, the mass ratio of aramid pulp to low-density polyethylene in the core layer is 1:(0.1-10), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any range between two values.
[0087] In the sheet material of the present invention, the lengths of the low-density polyethylene and aramid pulp in the core layer are both 50-200 nm (e.g., 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any range between two values).
[0088] In the sheet material of the present invention, the thickness of the core layer is 100-150 μm, for example, 100 μm, 102 μm, 104 μm, 106 μm, 108 μm, 110 μm, 112 μm, 114 μm, 116 μm, 118 μm, 120 μm, 122 μm, 124 μm, 126 μm, 128 μm, 130 μm, 132 μm, 134 μm, 136 μm, 138 μm, 140 μm, 142 μm, 144 μm, 146 μm, 148 μm, 150 μm or any two of these values, preferably 108-130 μm.
[0089] In the sheet of the present invention, the thickness of the coating layer is 10-100 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm or any two of these values, preferably 20-50 μm.
[0090] The total thickness of the sheet material of the present invention is 110-350 μm, for example 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195 μm, 200 μm, 205 μm, 208 μm, 210 μm, 215 μm, 220 μm, 225 μm, 230 μm, 235 μm. The range of μm, 240μm, 245μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350μm, or any two of these values, preferably 128-230μm, more preferably 165-208μm.
[0091] The interlaminar shear strength of the sheet material of the present invention is ≥45MPa, preferably 45-52MPa, for example 45MPa, 45.2MPa, 45.5MPa, 46MPa, 46.5MPa, 47MPa, 47.5MPa, 48MPa, 48.5MPa, 49MPa, 49.5MPa, 50MPa, 50.5MPa, 50.8MPa, 51MPa, 51.3MPa, 51.5MPa, 52MPa or any range between two values.
[0092] The sheet material of the present invention has a puncture resistance of ≥14N, preferably 14-19N, for example 14N, 14.3N, 14.5N, 14.9N, 15N, 15.5N, 16N, 16.5N, 17N, 17.5N, 18N, 18.5N, 18.7N, 19N or any range between two values.
[0093] Sheet preparation method
[0094] The sheet of the present invention can be prepared by the following method: aramid pulp and low-density polyethylene are dispersed in water to obtain a suspension, which is then finely ground and loosened, and a core layer is prepared by coating and drying. The core layer is then preheated, and high-density polyethylene is coated on one or two surfaces of the core layer. The sheet is then prepared by co-crystallization.
[0095] In some embodiments, the mass fraction of aramid pulp and low-density polyethylene in the suspension is 8%-15%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or any range between two values; wherein the mass fraction of aramid pulp in the suspension is 0.1%-14.9%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12%. The mass fraction of low-density polyethylene in the suspension is 0.1%-14.9%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 14.9%, or any two values.
[0096] In the method of this invention, fine grinding is preferably nano-fine grinding, and delamination is preferably high-frequency delamination. In this invention, high-frequency delamination refers to the process of mechanically dispersing aramid pulp and low-density polyethylene using a high-frequency delamination machine. The high-frequency delamination instrument used is a standard fiber dissociator from Guangdong Internesson Instruments Co., Ltd., and the rotation speed is 2000-3000 r / min. After nano-fine grinding, the length of the aramid pulp and low-density polyethylene of this invention is preferably controlled to be 50-200 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, or any range between two values.
[0097] In some embodiments, the drying temperature of the coating drying method is 80-90°C, such as 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, or any range between two values; the vacuum degree of the coating drying method is 10-1000Pa, such as 10Pa, 20Pa, 40Pa, 60Pa, 80Pa, 100Pa, 200Pa, 300Pa, 400Pa, 500Pa, 600Pa, 700Pa, 800Pa, 900Pa, 1000Pa, or any range between two values; the drying time of the coating drying method is 12-24h, such as 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any range between two values.
[0098] In some embodiments, the preheating temperature is 110-150°C, for example, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C or any range between two values, preferably 120-140°C.
[0099] In some embodiments, the co-crystallization temperature is 80-130°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, or any range between two values, preferably 90-110°C; the co-crystallization time is 1-20 min, for example, 1 min, 2 min, 4 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, or any range between two values, preferably 3-10 min. By introducing low-density polyethylene into the core layer, the core layer containing aramid pulp and low-density polyethylene co-crystallizes with the coating layer containing high-density polyethylene, which is beneficial for improving the interlaminar shear strength of the sheet and optimizing the composite compatibility.
[0100] In some preferred embodiments, the method for preparing the sheet of the present invention includes the following steps: Step 1: A certain mass of aramid pulp and low-density polyethylene are dispersed in water, processed using a nano-sand mill, and then fully dispersed using a high-frequency descaling machine. The core layer is then prepared using a coating and drying method. Step 2: Place the core layer obtained in Step 1 on a high-low temperature heating and cooling platform and preheat it to 110-150℃. Then, uniformly coat the upper and lower surfaces of the core layer obtained in Step 1 with high-density polyethylene. Then, rapidly cool the high-low temperature heating and cooling platform to 80-130℃ for co-crystallization. The co-crystallization time is 1-20 minutes, thus obtaining a three-layer sheet of aramid pulp / polyethylene with high compatibility.
[0101] In this invention, in order to improve the compatibility of the sheet material, aramid pulp and low-density polyethylene are first finely ground to nanoscale. Then, the nano-treated aramid pulp and polyethylene are placed together in water and fully dispersed using a high-frequency dispersing machine to inhibit agglomeration.
[0102] Subsequently, based on similar compatibility and under specific co-crystallization conditions, the low-density polyethylene in the core layer can form a eutectic structure with the high-density polyethylene coated on the surface at the phase interface, thereby improving interfacial compatibility. The sheet prepared by the molding process of this invention can increase the interlaminar shear strength to over 45 MPa and the puncture resistance to over 14 N.
[0103] Battery separator
[0104] The battery separator of the present invention comprises a core layer and a coating layer on one or both surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene. In some preferred embodiments, the battery separator of the present invention is prepared using the sheet material described in any embodiment of the present invention.
[0105] In the battery separator of the present invention, the sources of aramid pulp, low-density polyethylene and high-density polyethylene are the same as those of aramid pulp, low-density polyethylene and high-density polyethylene in the sheet.
[0106] In some preferred embodiments, the battery separator of the present invention uses commercially available aramid pulp, including but not limited to aramid 1313 pulp, aramid 1414 pulp, heterocyclic aramid pulp, etc., such as aramid 1414 pulp produced by Sinochem High Performance Fiber Materials Co., Ltd.
[0107] In some preferred embodiments, the polyolefin material used in the battery separator of the present invention is a commercially available low-density polyethylene, such as one or more of the following: 7047 produced by Daqing Petrochemical Company, 3224 produced by Formosa Plastics Corporation, 9020 produced by Tianjin United Company, and 1801 produced by Yangzi Petrochemical Company.
[0108] In some preferred embodiments, the polyolefin material used in the battery separator of the present invention is one or more of the following commercially available high-density polyethylene: 5200B, 2200J, and 5000S produced by Daqing Petrochemical Company; 5502, TR144, and TR480 produced by Shanghai Jinfei; 7000F produced by Yangzi Petrochemical; and 9001 produced by plastics.
[0109] The porosity of the battery separator is 40-60%, for example, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60% or any two of these values, preferably 47-58%.
[0110] In the battery separator of the present invention, the mass ratio of aramid pulp to low-density polyethylene in the core layer is 1:(0.1-10), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any range between two values.
[0111] In the battery separator of the present invention, the lengths of the low-density polyethylene and aramid pulp in the core layer are both 50-200 nm (e.g., 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or any range between two values).
[0112] The thickness of the battery separator of the present invention is 13-17 μm, for example, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or any range between two values; it should be understood that after the core layer and coating layer of the sheet are eutectic treated, they have become an integral structure, and it is impossible to test the specific parameters of each part of the battery separator. If the film is torn apart individually, it will also affect the authenticity of the data. Therefore, this article only limits the total thickness of the battery separator.
[0113] The average pore size of the battery separator of the present invention is less than 1 μm, preferably 620-740 nm, for example 620 nm, 630 nm, 640 nm, 650 nm, 660 nm, 670 nm, 671 nm, 672 nm, 673 nm, 674 nm, 675 nm, 676 nm, 677 nm, 678 nm, 679 nm, 680 nm, 690 nm, 700 nm, 715 nm, 720 nm, 730 nm, 731 nm, 732 nm, 733 nm, 734 nm, 735 nm, 736 nm, 737 nm, 738 nm, 739 nm, 740 nm or any range between two values.
[0114] The interlaminar shear strength of the battery separator of the present invention is 40-50 MPa, for example, 40 MPa, 41 MPa, 41.5 MPa, 42 MPa, 42.5 MPa, 42.7 MPa, 43 MPa, 43.5 MPa, 44 MPa, 44.5 MPa, 45 MPa, 45.1 MPa, 45.5 MPa, 46 MPa, 46.4 MPa, 46.5 MPa, 47 MPa, 47.5 MPa, 48 MPa, 50 MPa or any range of two values.
[0115] The puncture resistance of the battery separator of the present invention is 4.0-6.0N, for example, 4.0N, 4.2N, 4.4N, 4.6N, 4.8N, 5.0N, 5.1N, 5.2N, 5.3N, 5.4N, 5.5N, 5.6N, 5.7N, 5.8N, 5.9N, 6.0N or any range between two values.
[0116] The battery assembled from the battery separator of the present invention, after 500 charge-discharge cycle tests, has a specific capacity loss rate of less than 1%, preferably 0.3-0.9%, for example 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any range between two values.
[0117] The battery separator is prepared using the sheet material described in any embodiment of this document. In some embodiments, the preparation method is as described in any embodiment below.
[0118] Preparation method of battery separator
[0119] The battery separator of the present invention can be prepared by the following method: creating pores in the sheet material described in any embodiment of the present invention to obtain the battery separator.
[0120] In this invention, the hole-forming process employs a biaxial stretching technique, specifically including the following steps: S1: Preheated sheet; and S2: Synchronous bidirectional stretching.
[0121] In step S1, the preheating temperature is 50-70℃, for example, 50℃, 55℃, 60℃, 65℃, 70℃ or any range between two values, preferably 60-70℃; the preheating time is 20-60s, for example, 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s or any range between two values, preferably 20-40s.
[0122] In some preferred embodiments, in step S1, the sheet is cut to a suitable shape and size before preheating. More preferably, the sheet is square in shape, with a side length of 10-15cm, such as 10cm, 11cm, 12cm, 13cm, 14cm, 15cm or any range between two values.
[0123] In step S2, three simultaneous biaxial stretching operations are performed. The temperature for simultaneous biaxial stretching is 85-100℃, the stretching rate is 30-100% / s, the stretching ratio is 1.5-5.0, the heat setting temperature is 85-100℃, and the heat setting time for each operation is 10-240s.
[0124] In step S2, the temperatures of the second and third synchronous biaxial stretching are both higher than the temperature of the first synchronous biaxial stretching. The temperatures of the second and third synchronous biaxial stretching may be the same or different.
[0125] In step S2, the stretching rates of the first and second synchronous biaxial stretching are both higher than the stretching rate of the third synchronous biaxial stretching.
[0126] In step S2, the stretching ratio of the second synchronous biaxial stretching is greater than that of the first synchronous biaxial stretching, and the stretching ratio of the third synchronous biaxial stretching is greater than that of the second synchronous biaxial stretching.
[0127] In step S2, the heat setting temperature of the first and second synchronous biaxial stretching is higher than that of the third synchronous biaxial stretching, the heat setting temperature of the second synchronous biaxial stretching is higher than that of the first synchronous biaxial stretching, the heat setting temperature of the first synchronous biaxial stretching is the same as or different from that of the first synchronous biaxial stretching, and the heat setting temperature of the second synchronous biaxial stretching is the same as or different from that of the second synchronous biaxial stretching.
[0128] In step S2, the heat setting time for the third synchronous biaxial stretching is greater than the heat setting time for the first synchronous biaxial stretching and the heat setting time for the second synchronous biaxial stretching.
[0129] In some preferred embodiments, in step S2, the temperature of the first synchronous biaxial stretching is 85-95°C, for example, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, or any range between two values, preferably 85-90°C; the stretching rate is 50-100% / s, for example, 50% / s, 60% / s, 70% / s, 80% / s, 90% / s, 100% / s, or any range between two values, preferably 60-90% / s; and the stretching ratio is 1.5-2. 0, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any range between two values, preferably 1.8-2.0; the heat setting time is 10-60s, for example, 10s, 20s, 30s, 40s, 50s, 60s or any range between two values, preferably 10-30s; the heat setting temperature is 85-95℃, for example, 85℃, 86℃, 87℃, 88℃, 89℃, 90℃, 91℃, 92℃, 93℃, 94℃, 95℃ or any range between two values, preferably 85-90℃.
[0130] In some preferred embodiments, in step S2, the temperature of the second synchronous biaxial stretching is 90-100°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, or any range between two values, preferably 95-100°C; the stretching rate is 50-100% / s, for example, 50% / s, 60% / s, 70% / s, 80% / s, 90% / s, 100% / s, or any range between two values, preferably 80-100% / s; the stretching ratio is 2.1-2.5, for example... 2.1, 2.2, 2.3, 2.4, 2.5, or any range between two values, preferably 2.1-2.3; the heat setting time is 20-60s, for example 20s, 25s, 30s, 35s, 40s, 45s, 50s, 55s, 60s, or any range between two values, preferably 40-60s; the heat setting temperature is 90-100℃, for example 90℃, 91℃, 92℃, 93℃, 94℃, 95℃, 96℃, 97℃, 98℃, 99℃, 100℃, or any range between two values, preferably 95-100℃.
[0131] In some preferred embodiments, in step S2, the temperature of the third simultaneous biaxial stretching is 90-100°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, or any range between two values, preferably 95-100°C; the stretching rate is 30-60% / s, for example, 30% / s, 31% / s, 32% / s, 33% / s, 34% / s, 35% / s, 36% / s, 37% / s, 38% / s, etc. The value is 39% / s, 40% / s, 41% / s, 42% / s, 43% / s, 44% / s, 45% / s, 46% / s, 47% / s, 48% / s, 49% / s, 50% / s, 51% / s, 52% / s, 53% / s, 54% / s, 55% / s, 56% / s, 57% / s, 58% / s, 59% / s, 60% / s, or any range of two values, preferably 30-50% / s; the stretching ratio is 3.0-5.0, for example 3.0, 3. The values are 1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, or any range of two values, preferably 3.0-4.0; the heat setting time is 60-240s, for example, 60s, 70s, 80s, 90s, 100s, 110s, 120s, 130s, 140s, 150s, 160s, 170s, 180s. The heat setting temperature is 190s, 200s, 210s, 220s, 230s, 240s, or any range between two values, preferably 100-150s; the heat setting temperature is 70-90℃, for example, 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃, 80℃, 81℃, 82℃, 83℃, 84℃, 85℃, 86℃, 87℃, 88℃, 89℃, 90℃, or any range between two values, preferably 70-80℃. Unless otherwise specified, the heat setting temperature is consistent with the synchronous biaxial stretching heating zone temperature of the stretching machine.
[0132] It should be understood that in this article, when adjusting the stretch ratio, the thickness of the core layer and coating layer of the sheet should also be adjusted accordingly. This is because if the stretch ratio is large and the thickness of the core layer and coating layer is small, the drawn film will be too thin and have a large pore size, making it unusable.
[0133] In some preferred embodiments, the method for preparing the battery separator includes the following steps: Step 1: Cut the sheet material of the present invention into a square sheet of 13×13cm, place it in a biaxial stretching machine, and preheat it at 50-70℃ for 20-60s; Step 2: Heat the heating zone of the biaxial stretching machine to 85-95℃, and perform chain segment orientation on the sheet at a stretching rate of 50-100% / s and a stretching ratio of 1.5-2.0, and heat set it for 10-60s at this temperature. Step 3: Further heat the heating zone of the biaxial stretching machine to 90-100℃, and stress concentrate the sheet material that has initially completed the chain segment orientation at a stretching rate of 50-100% / s and a stretching ratio of 2.1-2.5, and heat set it for 20-60s under this temperature condition. Step 4: Maintain the heating zone temperature of the biaxial stretching machine at 90-100℃, and simultaneously biaxially stretch the stress-concentrated sheet at a stretching rate of 30-60% / s and a stretching ratio of 3.0-5.0 to create pores. After the average pore size of the resulting three-layer co-extruded film reaches the predetermined value (below 1μm, for example, 620-740nm), heat set at 70-90℃ for 60-240s to complete the preparation of a battery separator with high compatibility.
[0134] The pore-forming process of this invention adopts a synchronous biaxial stretching method. Synchronous biaxial stretching is beneficial for manufacturing pores with a near-circular shape, which is conducive to obtaining a battery separator with uniform pore size and improving its electrochemical performance.
[0135] The battery separator obtained by the synchronous biaxial stretching pore-forming process of the present invention has a thickness of 13-17 μm, a porosity of 40-60%, and an average pore size of less than 1 μm. The battery prepared by it has a specific capacity loss rate of less than 1% after 500 charge-discharge cycles. Therefore, the battery separator of the present invention is of great significance for solving the defects of traditional polyolefin separators and developing high energy density batteries.
[0136] In this invention, the uniform pore-forming process of the battery separator (aramid pulp / polyethylene battery separator) relies on the uniform dispersion and gradient orientation process of the aramid pulp in polyethylene. During biaxial synchronous stretching, the aramid pulp can be used as a stress concentration point, and by controlling process conditions such as stretching temperature, stretching rate, stretching ratio, heat setting temperature, and time, a battery separator modified with aramid pulp that has suitable pore size and uniform porosity can be prepared.
[0137] Battery
[0138] The battery of the present invention contains the battery separator described in any embodiment herein. Batteries suitable for the present invention include, but are not limited to, lithium-ion batteries. In some preferred embodiments, the battery suitable for the present invention is a lithium-sulfur battery. In some preferred embodiments, the lithium-ion battery of the present invention exhibits a specific capacity loss rate of less than 1% after 500 charge-discharge cycle tests.
[0139] use
[0140] In some embodiments, the present invention provides the use of aramid pulp, low-density polyethylene and high-density polyethylene in improving the puncture resistance and porosity of battery separators and reducing the specific capacity loss rate during battery charge-discharge cycles.
[0141] In some embodiments, the present invention provides the use of the sheet described in any of the embodiments herein in the preparation of battery separators.
[0142] In some embodiments, the present invention provides the use of low-density polyethylene, aramid pulp, and high-density polyethylene in the preparation of battery separators, wherein the battery separator has an interlaminar shear strength of 40-50 MPa, a puncture resistance of 4.0-6.0 N, and the battery prepared therefrom exhibits a specific capacity loss of less than 1% after 500 charge-discharge cycle tests. Preferably, the low-density polyethylene, aramid pulp, and high-density polyethylene are as described in any embodiment herein.
[0143] In some embodiments, the present invention provides the application of aramid pulp, low-density polyethylene and high-density polyethylene in the preparation of battery separators with a porosity of 40-60%, an average pore size of less than 1 μm, and a specific capacity loss rate of less than 1% after 500 charge-discharge cycles, an interlaminar shear strength of more than 40 MPa and a puncture resistance of more than 4.0 N.
[0144] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments are conventional methods, reagents, and materials in the art, unless otherwise stated. The raw material compounds in the embodiments are all commercially available.
[0145] In this invention, the aramid pulp in each embodiment and comparative example is aramid 1414 pulp produced by Sinochem High Performance Fiber Materials Co., Ltd., with a Canadian freeness of 340-460 mL and a specific surface area of 6.50-11.50 m². 2 / g.
[0146] Unless otherwise specified, in this invention, the low-density polyethylene in all embodiments and comparative examples is sourced from 7047 produced by Daqing Petrochemical Company, with a density of 0.92 g / cm³. 3 It has a melting point of 109℃ and a melt index of 6.7g / 10min.
[0147] Unless otherwise specified, in this invention, the high-density polyethylene used in all embodiments and comparative examples is 5200B produced by Daqing Petrochemical Company, with a density of 0.95 g / cm³. 3 It has a melting point of 135℃ and a melt index of 4.9 g / 10 min.
[0148] Example 1
[0149] S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 147±12nm and 126±8nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 130μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 30μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain a sheet with high compatibility. S3. Cut the sheet obtained in S2 into 13×13cm square sheets, place them in a biaxial synchronous stretching machine, and preheat at 60℃ for 40s; S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of a battery separator with high compatibility.
[0150] Example 2
[0151] S1. Disperse 15g of aramid pulp and 5g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 159±17nm and 144±20nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 125μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 20μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain a sheet with high compatibility. S3. Cut the sheet obtained in S2 into 13×13cm square sheets, place them in a biaxial synchronous stretching machine, and preheat at 60℃ for 40s; S4. Heat the heating zone of the biaxial synchronous stretching machine to 90°C, and heat-set it for 25 seconds at a stretching rate of 90% / s and a stretching ratio of 1.8 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 100°C, and heat-set it for 50 seconds at a stretching rate of 80% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 100°C and perform synchronous biaxial stretching at a stretching rate of 35% / s and a stretching ratio of 3.1. Then, heat set at 80°C for 120s to complete the preparation of a battery separator with high compatibility.
[0152] Example 3
[0153] S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 189±7nm and 122±16nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 108μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 50 μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain a sheet with high compatibility. S3. Cut the sheet obtained in S2 into 13×13cm square sheets, place them in a biaxial synchronous stretching machine, and preheat at 60℃ for 20s. S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 30 seconds at a stretching rate of 70% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 100°C, and heat-set it for 40 seconds at a stretching rate of 100% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 100°C and perform synchronous biaxial stretching at a stretching rate of 30% / s and a stretching ratio of 4.0. Then, heat set at 80°C for 150s to complete the preparation of a battery separator with high compatibility.
[0154] Example 4
[0155] S2, S3, S4, S5 and S6 of this embodiment are the same as those of embodiment 1, but the difference is that in step S1, 18g of aramid pulp and 2g of low-density polyethylene are dispersed in 180g of water and ground for 30min using a nano-milling machine. The lengths of the aramid pulp and the low-density polyethylene are 150±9nm and 122±13nm, respectively.
[0156] Example 5
[0157] S2, S3, S4, S5 and S6 of this embodiment are the same as those of embodiment 1, but the difference is that in step S1, 2g of aramid pulp and 18g of low-density polyethylene are dispersed in 180g of water and ground for 30min using a nano-milling machine. The lengths of the aramid pulp and the low-density polyethylene are 148±7nm and 131±10nm, respectively.
[0158] Example 6
[0159] S1, S3, S4, S5 and S6 of this embodiment are the same as those of embodiment 1, but the difference is that the co-crystallization temperature in step S2 is 130°C and the co-crystallization time is 10 min.
[0160] Example 7
[0161] S1, S3, S4, S5 and S6 of this embodiment are the same as those of embodiment 1, but the difference is that the co-crystallization temperature in step S2 is 80°C and the co-crystallization time is 3 min.
[0162] Example 8
[0163] Steps S1, S2, and S3 in this embodiment are the same as in embodiment 1. Steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 100% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 100% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 60% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0164] Example 9
[0165] Steps S1, S2, and S3 in this embodiment are the same as in embodiment 1. Steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 50% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 50% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 30% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0166] Example 10
[0167] S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 143±9nm and 137±12nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 150μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 50 μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain a sheet with high compatibility. S3. Cut the sheet obtained in S2 into 13×13cm square sheets, place them in a biaxial synchronous stretching machine, and preheat at 60℃ for 40s; S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 2.0 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.5 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 5.0. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0168] Example 11
[0169] S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 151±17nm and 146±14nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 150μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 30μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain a sheet with high compatibility. S3. Cut the sheet obtained in S2 into 13×13cm square sheets, place them in a biaxial synchronous stretching machine, and preheat at 60℃ for 40s; S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.5 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.1 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0170] Example 12
[0171] Steps S1, S2, and S3 in this embodiment are the same as in embodiment 1. Steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 95°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 100°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 100°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0172] Example 13
[0173] Steps S1, S2, and S3 in this embodiment are the same as in embodiment 1. Steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 90°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 90°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0174] Comparative Example 1
[0175] Steps S3, S4, S5, and S6 in this comparative example are the same as in Example 1, with steps S1 and S2 as follows: S1. Disperse 20g of aramid pulp in 180g of water, grind it for 30min using a nano-milling machine until the aramid pulp is 157±17nm, then decompose it in a high-frequency decomposition machine for 10min. Subsequently, precisely coat the aramid pulp aqueous solution onto a clean horizontal glass plate and dry it in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 110μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 80μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain the sheet.
[0176] Comparative Example 2
[0177] Steps S3, S4, S5, and S6 in this comparative example are the same as in Example 1, with steps S1 and S2 as follows: S1. Disperse 20g of low-density polyethylene in 180g of water, grind it for 30min using a nano-milling machine, and the length dimensions of the low-density polyethylene are 166±21nm. Then, decompose it in a high-frequency decomposition machine for 10min. Subsequently, the low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 115μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform that has been preheated to 120°C. Then, uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 60μm. After coating, rapidly cool the high-low temperature heating and cooling platform to 100°C and crystallize for 5 minutes to obtain the sheet.
[0178] Comparative Example 3
[0179] Steps S3, S4, S5, and S6 in this comparative example are the same as in Example 1, except that step S2 is omitted, and only step S1 is used, as follows: S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 109±5nm and 82±9nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain a single-layer sheet with a thickness of 282μm.
[0180] Comparative Example 4
[0181] Steps S3, S4, S5, and S6 in this comparative example are the same as in Example 1, with steps S1 and S2 as follows: S1. Disperse 10g of aramid pulp and 10g of low-density polyethylene in 180g of water. After grinding with a nano-milling machine for 30min, the lengths of the aramid pulp and the low-density polyethylene are 136±11nm and 142±23nm, respectively. Then, decompose in a high-frequency decomposition machine for 10min. Subsequently, the aramid pulp / low-density polyethylene aqueous solution is precisely coated on a clean horizontal glass plate and dried in a vacuum oven at 85℃ and 100Pa for 15h to obtain the core layer with a thickness of 130μm. S2. Place the core layer obtained in S1 on a high-low temperature heating and cooling platform at room temperature, and then uniformly coat the two surfaces of the core layer with completely molten high-density polyethylene with a coating thickness of 30μm to obtain a sheet material without co-crystallization treatment.
[0182] The interlaminar shear strength and puncture resistance of the sheet and battery separator in Comparative Example 4 both decreased, indicating the necessity of co-crystallization treatment.
[0183] Comparative Example 5
[0184] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 2.5 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 3.0 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 6.0. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0185] The battery separator in Comparative Example 5 was too thin due to excessive stretching during the preparation process, resulting in decreased puncture resistance, larger pore size, and excessive porosity.
[0186] Comparative Example 6
[0187] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.1 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 1.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 1.9. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0188] The battery separator in Comparative Example 6 had a smaller pore size and lower porosity due to an excessively low stretching ratio during the preparation process.
[0189] Comparative Example 7
[0190] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 120% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 150% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 72% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0191] The battery separator in Comparative Example 7 suffered from excessive stretching during the preparation process, resulting in decreased interlaminar shear strength and puncture resistance, as well as increased pore size and porosity.
[0192] Comparative Example 8
[0193] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 40% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 40% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 20% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0194] The battery separator in Comparative Example 8 had too small a pore size and porosity due to the excessively low stretching rate during the preparation process.
[0195] Comparative Example 9
[0196] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 75°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 80°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 80°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 60°C for 120s to complete the preparation of the battery separator.
[0197] The battery separator of Comparative Example 9 had poor puncture resistance and excessive pore size and porosity due to the low temperature during the preparation process.
[0198] Comparative Example 10
[0199] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 100°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 110°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 110°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 100°C for 120s to complete the preparation of the battery separator.
[0200] The battery separator in Comparative Example 10 had a smaller pore size and porosity due to excessively high temperature during the preparation process.
[0201] Comparative Example 11
[0202] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 40% / s and a stretching ratio of 1.1 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0203] Due to the small stretching rate and stretching ratio in step S4 of the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 11 are significantly reduced compared to Example 1, and the pore size is smaller than that of Example 1.
[0204] Comparative Example 12
[0205] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 110% / s and a stretching ratio of 3.0 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0206] Due to the large stretching rate and stretching ratio in step S5 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 12 are significantly reduced compared to Example 1, while the pore size and porosity are larger than those of Example 1.
[0207] Comparative Example 13
[0208] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 40% / s and a stretching ratio of 2.0 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 42% / s and a stretching ratio of 3.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0209] Due to the small stretching rate and stretching ratio in step S5 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 13 are significantly reduced compared to Example 1, and the pore size is smaller than that of Example 1.
[0210] Comparative Example 14
[0211] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 70% / s and a stretching ratio of 5.5. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0212] Due to the large stretching rate and stretching ratio in step S6 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 14 are significantly reduced compared to Example 1, while the pore size and porosity are larger than those of Example 1.
[0213] Comparative Example 15
[0214] Steps S1, S2, and S3 in this comparative example are the same as in Example 1, while steps S4, S5, and S6 are as follows: S4. Heat the heating zone of the biaxial synchronous stretching machine to 85°C, and heat-set it for 25 seconds at a stretching rate of 60% / s and a stretching ratio of 1.9 to complete the chain segment orientation of the sheet. S5. Heat the heating zone of the biaxial synchronous stretching machine to 97°C, and heat-set it for 50 seconds at a stretching rate of 90% / s and a stretching ratio of 2.2 to complete the stress concentration of the sheet. S6. Keep the heating zone of the biaxial synchronous stretching machine at 97°C and perform synchronous biaxial stretching at a stretching rate of 25% / s and a stretching ratio of 2.3. Then, heat set at 75°C for 120s to complete the preparation of the battery separator.
[0215] Due to the smaller stretching rate and stretching ratio in step S6 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 15 are significantly reduced compared to Example 1, while the pore size and porosity are smaller.
[0216] Comparative Example 16
[0217] S1, S3, S4, S5 and S6 of this comparative example are the same as those of Example 1, but the difference is that the co-crystallization temperature in step S2 is 140°C and the co-crystallization time is 40 min.
[0218] Due to the excessively high co-crystallization temperature in step S2 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 16 were significantly lower than those in Example 1.
[0219] Comparative Example 17
[0220] S1, S3, S4, S5 and S6 of this comparative example are the same as those of Example 1, but the difference is that the co-crystallization temperature in step S2 is 70°C and the co-crystallization time is 1 min.
[0221] Due to the excessively low co-crystallization temperature in step S2 during the preparation process, the interlaminar shear strength and puncture resistance of the battery separator in Comparative Example 17 were significantly lower than those in Example 1.
[0222] Comparative Example 18
[0223] S2, S3, S4, S5, and S6 of this comparative example are the same as those of Example 1, except that in step S1, 1g of aramid pulp and 19g of low-density polyethylene are dispersed in 180g of water and ground for 30min using a nano-milling machine. The lengths of the aramid pulp and the low-density polyethylene are 143±14nm and 135±9nm, respectively.
[0224] The battery separator of Comparative Example 18 showed a significant decrease in puncture resistance compared to Example 1 because the aramid pulp content in step S1 of the preparation process was too low.
[0225] Comparative Example 19
[0226] S2, S3, S4, S5, and S6 of this comparative example are the same as those of Example 1, except that in step S1, 18.75g of aramid pulp and 1.25g of low-density polyethylene are dispersed in 180g of water and ground for 30min using a nano-milling machine. The lengths of the aramid pulp and the low-density polyethylene are 139±17nm and 130±8nm, respectively.
[0227] Due to the excessively high content of aramid pulp in step S1 during the preparation process, the interlaminar shear strength of the battery separator in Comparative Example 19 was significantly lower than that in Example 1, while the pore size and porosity were higher.
[0228] Test case
[0229] In this paper, the melt flow index was tested according to ISO 1872-2 standard; the density was tested according to GB 1033.2-2010 standard; the melting point was tested according to GB 19466.3-2009 standard; the Canadian freeness was tested according to TAPPI 227 standard; and the specific surface area was tested according to GB / T 19587 standard.
[0230] The lengths of the aramid pulp and low-density polyethylene were measured using a Hitachi SU5000 scanning electron microscope.
[0231] The thickness of the sheet material and battery separator was measured using a CHY-CA type automatic thin film thickness gauge from Jinan Xinzhun Instrument Equipment Co., Ltd.
[0232] The interlaminar shear strength of the sheet and battery separator was tested according to GB / T 1450.1-2005 standard.
[0233] The puncture resistance of the sheet and battery separator was measured using the GB / T 6672-2001 standard.
[0234] The pore size of the battery separator was measured using a Hitachi SU5000 scanning electron microscope.
[0235] The porosity of the battery separator was determined using the n-butanol absorption method. The specific testing method is as follows: The prepared battery separator material was cut into circular pieces with a diameter of 2 cm, and its original mass was recorded as m. s The resulting battery separator was then immersed in standard n-butanol for 2 hours to allow it to fully absorb the solvent. Excess solvent was then wiped off the separator surface with filter paper, and its mass was recorded as m. w Porosity can be calculated using the following formula: Porosity =
[0236] Where m s For dry film quality, m w For wet film quality, V s ρ is the volume of the diaphragm. b The density of n-butanol is 0.81 g / cm³. 3 .
[0237] The specific test method for the specific capacity loss rate after 500 charge-discharge cycles is as follows: (1) The reference for battery assembly is: Li Weiwei, Research on the structural regulation of aramid nanofiber-based lithium-sulfur battery separator and its suppression of polysulfide shuttle effect [D], Shaanxi University of Science and Technology.
[0238] Battery assembly was completed in a glove box, where the water and oxygen content was required to be less than 0.1 ppm. All assembled batteries were of the CR-2025 type. The prepared active material-containing electrode was used as the positive electrode, lithium metal as the standard negative electrode, and the electrolyte was an LS-002 type lithium bis(trifluoromethanesulfonyl)imide solution. The solvent used was a 1:1 volume ratio of dioxolane and ethylene glycol dimethyl ether, and the additive was 1% lithium nitrate. Each battery required a total electrolyte volume of 25 μL. After assembly, the batteries were sealed tightly and then allowed to stand for 12 hours before relevant performance tests were conducted.
[0239] (2) The CT3002A type Blue Electric system of Wuhan Blue Electric Battery System was used to conduct repeated charge-discharge cycle tests on the batteries composed of the separators of each embodiment and each comparative embodiment under a current density of 0.5C. The initial specific capacity of the battery before cycling was recorded. After 500 cycles, the battery system automatically read the current specific capacity of the battery, which is the specific capacity after 500 charge-discharge cycles. The formula for calculating the specific capacity loss rate after 500 charge-discharge cycles is as follows:
[0240] The physical parameters of the sheets and battery separators in each embodiment and comparative example are summarized in Table 1.
[0241] Table 1: Physical parameters of the sheet and battery separator in each embodiment and comparative example
[0242] The performance test results of the sheets and battery separators in each embodiment and comparative example are summarized in Table 2.
[0243] Table 2: Performance test results of sheet materials and battery separators in each embodiment and comparative example
[0244] As shown in Table 2, the core layer of Comparative Example 1 lacks low-density polyethylene, preventing the formation of a eutectic structure. Consequently, the interlaminar shear strength decreases significantly, and the pore size increases. Compared to Comparative Example 1, the stable existence of the eutectic structure between high- and low-density polyethylene in each embodiment significantly improves the interlaminar shear strength of the sheet material with aramid pulp / low-density polyethylene as the core layer and high-density polyethylene as the outer layer. This addresses the poor compatibility of aramid-based composite materials and the excessive stress concentration problem when aramid pulp is used alone as a three-layer co-extruded core material. While no aramid pulp was added to the core layer in Comparative Example 2, aramid pulp was added to the core layer in the embodiments. Due to the high strength and puncture resistance of aramid, and the ability of nano-milling and high-frequency dispersion to uniformly disperse the aramid pulp within the polyethylene core layer, it acts as a stress concentration point. Therefore, the battery separators in each embodiment exhibit superior puncture resistance, pore size, and porosity compared to Comparative Example 2. The sheet in Comparative Example 3 lacks high-density polyethylene coating on both surfaces. Without this coating and due to the high stress concentration in the aramid pulp, the sheet in Comparative Example 3 cannot form appropriately sized and uniform pores during simultaneous biaxial stretching, resulting in a significant loss of specific capacity during battery charging and discharging. The sheet in Comparative Example 4 was not eutectic treated. Compared to Examples 1-13, the untreated sheet in Comparative Example 4 has lower interlaminar shear strength, severely affecting composite compatibility. Data from Examples 1 and Comparative Examples 5-8 and 11-15 show that overstretching or insufficient stretching ratios affect the pore size, uniformity, and porosity of the battery separator, thus adversely impacting the practical application of the aramid pulp-modified battery separator described in this invention. Data from Examples 1 and Comparative Examples 9-10 and 16-17 show that excessively high or low temperatures during simultaneous biaxial stretching and subsequent heat setting and eutectic temperatures affect the final performance of the battery separator of this invention. As can be seen from the data in Example 1 and Comparative Examples 18-19, excessively high or low amounts of aramid pulp addition can affect the final performance of the battery separator of this invention. In summary, the preparation method conforming to the process parameter range of this invention can facilitate the preparation of battery separators with the excellent performance of this invention.
Claims
1. A sheet material, characterized in that, The sheet includes a core layer and a coating layer on one or both surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene.
2. The sheet as described in claim 1, characterized in that, The sheet material has one or more of the following characteristics: The aramid pulp has a Canadian free degree of 300-500 mL and a specific surface area of 6.00-12.00 m². 2 / g; The density of the high-density polyethylene is 0.94-0.96 g / cm³. 3 Its melting point is 130-137℃, and its melt index is 3-15g / 10min; The density of the low-density polyethylene is 0.91-0.93 g / cm³. 3 Its melting point is 105-115℃, and its melt index is 3-10g / 10min; In the core layer, the lengths of both the aramid pulp and the low-density polyethylene are 50-200 nm. In the core layer, the mass ratio of aramid pulp to low-density polyethylene is 1:(0.1-10); The thickness of the core layer is 100-150 μm, preferably 108-130 μm; The thickness of the coating layer is 10-100 μm, preferably 20-50 μm; The thickness of the sheet is 110-350 μm, preferably 128-230 μm; The interlaminar shear strength of the sheet is ≥45MPa; The sheet has a puncture resistance of ≥14N.
3. A method for preparing the sheet according to claim 1 or 2, characterized in that, The method includes dispersing aramid pulp and low-density polyethylene in water to obtain a suspension, which is then finely ground and loosened. A core layer is prepared by coating and drying. The core layer is then preheated, and high-density polyethylene is coated on one or two surfaces of the core layer. A sheet is then prepared by co-crystallization.
4. The method as described in claim 3, characterized in that, The method has one or more of the following characteristics: The aramid pulp and low-density polyethylene in the suspension have a mass fraction of 8%-15%; wherein the aramid pulp and low-density polyethylene in the suspension have a mass fraction of 0.1%-14.9% and a mass fraction of 0.1%-14.9% respectively. The fine grinding is nano-fine grinding, and / or the spalling is high-frequency spalling; The drying temperature of the coating drying method is 80-90℃; the vacuum degree of the coating drying method is 10-1000Pa; and the drying time of the coating drying method is 12-24h. The preheating temperature is 110-150℃, preferably 120-140℃; The temperature for co-crystallization is 80-130℃, preferably 90-110℃; the time for co-crystallization is 1-20 min, preferably 3-10 min. The lengths of both the aramid pulp and the low-density polyethylene after fine grinding are 50-200 nm.
5. A battery separator, characterized in that, The battery separator includes a core layer and a coating layer on one or two surfaces of the core layer; the core layer is made of low-density polyethylene and aramid pulp, and the coating layer is made of high-density polyethylene; preferably, the battery separator is prepared using the sheet material as described in claim 1 or 2.
6. The battery separator as described in claim 5, characterized in that, The battery separator has one or more of the following characteristics: The aramid pulp has a Canadian free degree of 300-500 mL and a specific surface area of 6.00-12.00 m². 2 / g; The density of the high-density polyethylene is 0.94-0.96 g / cm³. 3 Its melting point is 130-137℃, and its melt index is 3-15g / 10min; The density of the low-density polyethylene is 0.91-0.93 g / cm³. 3 Its melting point is 105-115℃, and its melt index is 3-10g / 10min; The porosity of the battery separator is 40-60%, preferably 47-58%; In the core layer, the lengths of both the aramid pulp and the low-density polyethylene are 50-200 nm. In the core layer, the mass ratio of aramid pulp to low-density polyethylene is 1:(0.1-10); The thickness of the battery separator is 13-17 μm; The average pore size of the battery separator is less than 1 μm, preferably 620-740 nm; The interlaminar shear strength of the battery separator is 40-50 MPa; The battery separator has a puncture resistance of 4.0-6.0N.
7. A method for preparing the battery separator according to claim 5 or 6, characterized in that, The method includes creating pores in the sheet according to claim 1 or 2 to obtain a battery separator; optionally, the method further includes the step of preparing the sheet using the method according to claim 3 or 4.
8. The method as described in claim 7, characterized in that, The hole-making process includes the following steps: S1: Preheated sheet; and S2: Synchronous bidirectional tension; Preferably, the synchronous biaxial stretching temperature is 85-100℃, the stretching rate is 30-100% / s, the stretching ratio is 1.5-5.0, the heat setting temperature is 85-100℃, and the heat setting time is 10-240s. Preferably, the method has one or more of the following features: In step S1, the preheating temperature is 50-70℃, more preferably 60-70℃; the preheating time is 20-60s, more preferably 20-40s. In step S2, three simultaneous biaxial stretching operations are performed; the temperatures of the second and third simultaneous biaxial stretching operations are both higher than the temperature of the first simultaneous biaxial stretching operation, and the temperatures of the second and third simultaneous biaxial stretching operations may be the same or different; and / or, the stretching rates of the first and second simultaneous biaxial stretching operations are both higher than the stretching rate of the third simultaneous biaxial stretching operation; and / or, the stretching ratio of the second simultaneous biaxial stretching operation is greater than the stretching ratio of the first simultaneous biaxial stretching operation, and the stretching ratio of the third simultaneous biaxial stretching operation is greater than the stretching ratio of the second simultaneous biaxial stretching operation; and / or, the heat setting temperatures of the first and second simultaneous biaxial stretching operations are higher than the heat setting temperature of the third simultaneous biaxial stretching operation, the heat setting temperature of the second simultaneous biaxial stretching operation is higher than the heat setting temperature of the first simultaneous biaxial stretching operation, the heat setting temperature of the first simultaneous biaxial stretching operation is the same or different from the temperature of the first simultaneous biaxial stretching operation, and the heat setting temperature of the second simultaneous biaxial stretching operation is the same or different from the temperature of the second simultaneous biaxial stretching operation; and / or, the heat setting time of the third simultaneous biaxial stretching operation is greater than the heat setting time of the first and second simultaneous biaxial stretching operations. Preferably, in step S2, the temperature of the first synchronous biaxial stretching is 85-95℃, more preferably 85-90℃; the stretching rate is 50-100% / s, more preferably 60-90% / s; the stretch ratio is 1.5-2.0, more preferably 1.8-2.0; the heat setting time is 10-60s, more preferably 10-30s; and the heat setting temperature is 85-95℃, more preferably 85-90℃. The temperature of the second synchronous biaxial stretching is 90-100℃, more preferably 95-100℃; the stretching rate is 50-100% / s, more preferably 80-100% / s; and the stretch ratio is... The heat setting time is 2.1-2.5, more preferably 2.1-2.3; the heat setting time is 20-60s, more preferably 40-60s; the heat setting temperature is 90-100℃, more preferably 95-100℃; the temperature of the third synchronous biaxial stretching is 90-100℃, more preferably 95-100℃; the stretching rate is 30-60% / s, more preferably 30-50% / s; the stretching ratio is 3.0-5.0, more preferably 3.0-4.0; the heat setting time is 60-240s, more preferably 100-150s; the heat setting temperature is 70-90℃, more preferably 70-80℃.
9. A lithium-ion battery, characterized in that, The lithium-ion battery includes the battery separator as described in claim 5 or 6; Preferably, the lithium-ion battery is a lithium-sulfur battery; Preferably, the specific capacity loss rate of the lithium-ion battery after 500 charge-discharge cycles is less than 1%.
10. Selected from the following applications: (1) The application of the sheet material according to claim 1 or 2 in improving the puncture resistance, porosity and reducing the specific capacity loss rate of the battery separator under charge-discharge cycles; (2) The application of the sheet material according to claim 1 or 2 in the preparation of battery separators; (3) Application of low-density polyethylene, aramid pulp and high-density polyethylene in the preparation of battery separators; preferably, the low-density polyethylene, aramid pulp and high-density polyethylene are as described in claim 2; in, The battery separator has an interlaminar shear strength of 40-50 MPa and a puncture resistance of 4.0-6.0 N. The battery prepared from it has a specific capacity loss rate of less than 1% after 500 charge-discharge cycles.